PERKEMBANGAN ALIRAN/PAHAM KEAGAMAAN DI SUMATERA BARAT - M. Agus Noorbani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2014)
Minangkabau traditional governance system were consists of many villages, where decision-making should be based on consensus agreement, so there is no centralized in Minangkabau tradition, making this area a heaven for the development of thought. The tradition subsequently raises the religious ideology head up. This qualitative descriptive study tried to examine the development of religious schools in this area. Religious thoughts and groups in West Sumatra more oriented toward moral improvement. These religious group were develop in an exclusive way, wereupon giving rise the prejudice in a society that often bring small ripples of social conflict. But the egalitarian attitude that has been as a tradition is able to prevent a larger conflict. Religious and political elites who represented by government using the pattern were used during the New Order to overcome these religious groups. Groups that destabilize is considered heretical disconnected often lead to banning.